2016
DOI: 10.4172/2576-1471.1000124
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Palmitate Synthesis Supports Oncogenic Signalling and Tumor Growth Through Diverse Mechanisms: Implications for FASN-Targeted Therapeutics

Abstract: Palmitate, the enzymatic product of fatty acid synthase (FASN), provides a substrate for the synthesis of longand short-chain fatty acids. Many recent studies have expanded our knowledge about the roles palmitate and lipid synthesis play in tumor cell biology beyond supporting energy metabolism and membrane building [1,2]. The recent article by Ventura and colleagues [3] described cell biology and pharmacology studies using a novel, selective small molecule FASN inhibitor, TVB-3166. They demonstrated that FASN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Fatty acid synthase plays an important role in tumor cell development and survival because it provides palmitic acids needed for the synthesis of membrane phospholipids during rapid cell growth and proliferation. Moreover, endogenously synthesized fatty acids act as posttranslational protein modifiers and modulate gene expression (24). Palmitate and palmitate-derived lipids are known to play essential roles in modulating signal transduction and function of proteins associated with signaling pathways that regulate cell growth and survival (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fatty acid synthase plays an important role in tumor cell development and survival because it provides palmitic acids needed for the synthesis of membrane phospholipids during rapid cell growth and proliferation. Moreover, endogenously synthesized fatty acids act as posttranslational protein modifiers and modulate gene expression (24). Palmitate and palmitate-derived lipids are known to play essential roles in modulating signal transduction and function of proteins associated with signaling pathways that regulate cell growth and survival (24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endogenously synthesized fatty acids act as posttranslational protein modifiers and modulate gene expression (24). Palmitate and palmitate-derived lipids are known to play essential roles in modulating signal transduction and function of proteins associated with signaling pathways that regulate cell growth and survival (24). Furthermore, recent studies have suggested that endogenously synthesized fatty acids are utilized by β-oxidation in CRC cells, which supports cancer cell survival, particularly under conditions of energy stress (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations